Encyclopedia of feminist literature - Whitson, Kathy J. (Greenwood Press, 2004)
A reference guide to the history and development of feminist literature, this book covers a wide range of works and genres, including novels, short stories, poetry, plays, and criticism. It focuses on the feminist works from writers such as Willa Cather, George Eliot, and Helen Keller.
Keywords: arts; cours; cycles supérieurs; discipline; fem7000; genre; identités LGBTQIA2+; outils; ouvrages de références; ressource en ligne; thématiques; études littéraires